Graphene nanoplatelets in hybrid composites: a review of mechanical and vibrational enhancements, challenges, and future prospects - Atallah, Kamel Eddine; Mohd Firdaus, Hassan; Siregar, Januar Perlaungan; Ouinas, Djamel (Institute of Physics, 2026)
This review presents a comprehensive and critical assessment of studies published between 2015 and 2025 on the integration of graphene nanoplatelets (GNP) into carbon fibre-reinforced polymers (CFRP), natural fibre-reinforced polymers (NFRP), and their hybrid laminates. The objective is to evaluate how GNP type, loading level, and dispersion approach influence the mechanical and vibrational performance of these composite systems. The literature was gathered through targeted searches of major scientific databases using keywords related to GNP, hybrid composites, mechanical behaviour, and vibration damping. The collected studies consistently report improvements in tensile properties, flexural performance, interlaminar shear strength, and damping capacity. Typical gains include a 15%–30% increase in interlaminar shear strength and a 50%–100% increase in damping ratio when GNP are uniformly dispersed and well bonded within the matrix or at fibre interfaces. Despite these advances, several gaps remain, including the limited use of natural fibres beyond flax, the lack of systematic multi-objective optimisation, and the absence of long-term durability assessments for GNP-reinforced hybrid systems. Challenges related to dispersion quality, manufacturing scalability, and cost also persist. This review outlines these limitations and highlights research directions that may support the development of reliable, multifunctional hybrid composites that balance performance, sustainability, and practical manufacturability.